A novel lytic polysaccharide monooxygenase from enrichment microbiota and its application for shrimp shell powder biodegradation - Zhang, Yang; Pan, Delong; Xiao, Peiyao; Xu, Qianqian; Geng, Fan; Zhang, Xinyu; Zhou, Xiuling; Xu, Hong (Frontiers in Microbiology, 2023)
Lytic polysaccharide monooxygenases (LPMO) are expected to change the current status of chitin resource utilization. This study reports that targeted enrichment of the microbiota was performed with chitin by the selective gradient culture technique, and a novel LPMO (M2822) was identified from the enrichment microbiota metagenome. First, soil samples were screened based on soil bacterial species and chitinase biodiversity. Then gradient enrichment culture with different chitin concentrations was carried out. The efficiency of chitin powder degradation was increased by 10.67 times through enrichment, and chitin degradation species Chitiniphilus and Chitinolyticbacter were enriched significantly. A novel LPMO (M2822) was found in the metagenome of the enriched microbiota. Phylogenetic analysis showed that M2822 had a unique phylogenetic position in auxiliary activity (AA) 10 family. The analysis of enzymatic hydrolysate showed that M2822 had chitin activity. When M2822 synergized with commercial chitinase to degrade chitin, the yield of N-acetyl glycosamine was 83.6% higher than chitinase alone. The optimum temperature and pH for M2822 activity were 35 °C and 6.0. The synergistic action of M2822 and chitin-degrading enzymes secreted by Chitiniphilus sp. LZ32 could efficiently hydrolyze shrimp shell powder. After 12 h of enzymatic hydrolysis, chitin oligosaccharides (COS) yield reached 4724 μg/mL. To our knowledge, this work is the first study to mine chitin activity LPMO in the metagenome of enriched microbiota. The obtained M2822 showed application prospects in the efficient production of COS.